Priming of microglia by type II interferon is lasting and resistant to modulation by interleukin-10 in situ - Hemmerich, Marc; Malorny, Nikolai; Lewen, Andrea; Hollnagel, Jan-Oliver; Chausse de Freitas, Bruno; Kann, Oliver (Journal of neuroimmunology, 2022)
Immunological priming by type II interferon (IFN-γ) is crucial for evoking neurotoxic phenotypes of microglia (tissue-resident macrophages). We report that serial exposure of hippocampal slice cultures to IFN-γ and lipopolysaccharide (Toll-like receptor 4 ligand) induces high release of IL-6, TNF-α and nitric oxide, concomitant loss of electrical network activity (neuronal gamma oscillations) and neurodegeneration. Notably, these effects are still present after 3 days of IFN-γ removal but neither mimicked by IFN-α nor attenuated by anti-inflammatory cytokine, IL-10. Our findings might be relevant for brain diseases featuring elevated IFN-γ levels, such as viral and bacterial infections, multiple sclerosis and Alzheimer's disease.
Gesehen am 21.06.2022